The Effect of Steroid and Mannitol Combination Treatment on Postoperative Rehabilitation of Multiple Metacarpal Bone Fractures - Jangyoun Choi; Hye Jin Seo; Jongweon Shin; Jun-Hee Byun; Sung No Jung (Medicina, 2023)
Background and Objectives: The expedient resolution of postoperative soft tissue edema is particularly important in hand surgery. Prolonged edema and pain become an obstacle to postoperative rehabilitation, delay return to daily life, and in severe cases, lead to a permanent decrease in range of motion. Based on the common physiology between postoperative hand swelling and complex regional pain syndrome (CRPS), we sought to determine if postoperative mannitol and steroid administration to multiple metacarpal bone fracture patients effectively reduces hand swelling and pain and is beneficial for hand rehabilitation. Materials and Methods: From March 2015 to February 2019, 21 patients who received closed pinning for multiple metacarpal fractures were included in a retrospective cohort study. The control group (n = 11) underwent a routine recovery, while the treatment group (n = 10) received dexamethasone and mannitol injections for five days postoperatively. Serial changes in the degree of pain and fingertip-to-palm distance (FPD) were measured in both groups. The duration from surgery to the initiation of rehabilitation and time to full grip was also compared. Results: Compared to the control, the treatment group showed a faster alleviation of pain scores from the postoperative fifth day (2.91 versus 1.80, p = 0.013), and faster recovery of FPD from postoperative two weeks (3.27 versus 1.90, p = 0.002). Time to physical therapy initiation (6.73 versus 3.80 days, p = 0.002) and full grip achievement (42.46 versus 32.70 days, p = 0.002) were also faster in the treatment group. Conclusions: The steroid-mannitol combination treatment for multiple metacarpal bone fracture patients in the acute postoperative phase promoted the reduction of hand edema and pain, leading to the earlier initiation of physical therapy, rapid improvement in joint motion, and faster achievement of full grip.